Photoreceptor-specific light adaptation of critical flicker frequency in trichromat and dichromat observers - Huchzermeyer, Cord; Martins, Cristiane M. G.; Nagy, Balazs; Barboni, Mirella T. S.; Ventura, Dora F.; Costa, Marcelo F.; Kremers, Jan (Journal of the Optical Society of America A-Optics Image Science and Vision, 2018)
The silent substitution paradigm offers possibilities to investigate and compare the temporal properties of mechanisms driven by single photoreceptor types, including the critical flicker frequency (CFF), in which the state of adaptation can be kept as invariant. We have (1) measured CFFs using triple silent substitutions to isolate L-, M-, and S-cone as well as rod-driven pathways under identical mean luminances and chromaticities; (2) repeated the CFF measurements at different mean luminances in order to validate the Ferry-Porter law (stating that the relationship between CFF and the log retinal illuminance-log I-is linear); and (3) compared these CFF versus log I functions for L-, M-, S-cone-, and rod-isolating stimuli for five trichromats and four X-linked dichromats (two protanopes, two deuteranopes). We show that the effects of luminance on the CFFs with silent substitution are comparable to those measured previously with chromatic stimuli. We found that M-cone-driven CFFs are smaller in trichromats than in protanopes. Furthermore, the slopes of the M-cone-driven CFF versus log I functions are smaller in trichromats. Possibly, the lacking L-cones are replaced by M-cones in these two protanopes and the CFF depends on cone density. Furthermore, we found that in trichromats, the slopes of the CFF-log I functions are smaller for M-cone-than for L-cone-isolating stimuli. This contradicts the current interpretation of the CFF-log I functions for chromatic stimuli, which states that CFF is mediated by the most strongly modulated photoreceptor type. Thus, the larger slopes that were previously found with medium-wavelength chromatic stimuli compared with long-wavelength chromatic stimuli seem to be the result of an addition of signals from different photoreceptors and do not necessarily result from M-cones being inherently faster. (C) 2018 Optical Society of America